Characteristics and outcomes of aortic stenosis patients with and without stroke. (25th January 2023) - Goh, F Q; Sia, C H; Tan, B Y Q; Yeo, L L L; Sharma, V K; Chew, N W S; Li, T Y W; Ngiam, J N; Yeo, T C; Kong, W K F; Poh, K K
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Sia CH was supported by the National University of Singapore Yong Loo Lin School of Medicine's Junior Academic Faculty Scheme Background: Aortic stenosis (AS) is related to several atherosclerosis risk factors and is associated with an increased risk of ischaemic stroke. Some reports suggest that aortic valve calcification may predispose to embolic stroke although this is not well-studied. The literature is also sparse regarding individual stroke subtypes and predictors of stroke in AS. Purpose: We aimed to 1) Describe rates of ischaemic stroke in AS including specific stroke subtypes; 2) Compare clinical and echocardiographic characteristics of patients with AS who subsequently developed ischaemic stroke versus those who did not, and 3) Identify independent variables associated with subsequent stroke in AS. Methods: Patients with AS were recruited from an echocardiography database from September 2011 to December 2015 at a single tertiary centre. The primary study endpoint was acute ischaemic stroke. Clinical characteristics and echocardiographic parameters were compared between patients who suffered a stroke after AS diagnosis and those who did not. Multivariable Cox regression analysis was used to identify factors associated with subsequent stroke. Results: A total of 703 patients with AS were studied, with a median follow-up duration of 3.0 (IQR 0.5, 5.0) years. Twenty-two patients (3.1%) developed stroke following AS diagnosis (large vessel, 18.2%; cardioembolic, 50.0%; small vessel, 18.2%; other determined ischaemic stroke, 13.6%). These patients had a greater prevalence of previous stroke or transient ischaemic attack (TIA) (50.0%) compared to patients who did not develop subsequent stroke (20.9%), p<0.001. Patients with AS who developed subsequent stroke also more commonly had atrial fibrillation at the time of indexed echocardiography (40.0%) compared to their counterparts who did not develop stroke (13.5%), p=0.004 (Table 1). Other cardiovascular risk factors and traditional echocardiographic parameters of AS severity were similar between the 2 groups. Degenerative calcified aortic valve was not associated with the development of all types of ischaemic stroke or cardioembolic stroke. AS severity was also not associated with development of stroke. Multivariable Cox regression analysis found previous stroke or TIA (HR 8.00, 95% CI 2.70–23.58, p<0.001) and atrial fibrillation at time of echocardiography (HR 8.81, 95% CI 1.34–10.80, p=0.012) to be independent predictors of subsequent stroke in AS. The key findings of our study are summarised in Figure 1. Conclusions: Cardioembolic stroke is the most common stroke subtype in patients with AS. Previous history of stroke or TIA and atrial fibrillation at time of diagnostic echocardiography are independent predictors of subsequent stroke in AS. Calcified aortic valve was not found to be a risk factor for all types of ischaemic stroke or cardioembolic stroke. Table 1 Figure 1